1988
DOI: 10.1007/bf00535138
|View full text |Cite
|
Sign up to set email alerts
|

The requirement for epimastigote attachment during division and metacyclogenesis in Trypanosoma congolense

Abstract: In cultures of tsetse proboscis stages during the development of Trypanosoma congolense, attached epimastigote forms multiply and give rise to free nondividing metacyclic trypanosomes. Prevention of attachment by shaking the cultures or by providing a polypropylene substratum does not inhibit epimastigote division but does prevent the differentiation of metacyclics. We conclude that epimastigote attachment forms a necessary part of the program of metacyclic development.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
0

Year Published

1990
1990
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 13 publications
2
25
0
Order By: Relevance
“…This echoes the observations from in vitro studies where epimastigotes are reported to contract and shorten soon after attachment to the plastic substratum and then to lengthen after a few days [26,30,31]. In live trypanosomes the elongated posterior had a rigid appearance, contrasting with the fluid undulating motion of trypomastigotes (Additional file 6: Movie 1).…”
Section: Resultssupporting
confidence: 83%
See 1 more Smart Citation
“…This echoes the observations from in vitro studies where epimastigotes are reported to contract and shorten soon after attachment to the plastic substratum and then to lengthen after a few days [26,30,31]. In live trypanosomes the elongated posterior had a rigid appearance, contrasting with the fluid undulating motion of trypomastigotes (Additional file 6: Movie 1).…”
Section: Resultssupporting
confidence: 83%
“…EM studies show that attachment of T. congolense epimastigotes is via hemidesmosomes both in vitro and in vivo [20,22,29]. Comparison of shaken and unshaken cultures showed that attachment is not necessary for epimastigote division but is a prerequisite for differentiation into metacyclics [30]. The question whether the in vitro produced life cycle stages of T. congolense represent those produced in the fly has been addressed by comparison of morphology at the light and ultrastructural levels, and immunocytological analysis of the VSG coats of metacyclics [20,26,31].…”
Section: Introductionmentioning
confidence: 99%
“…The expertise and skills are needed for the study of small size individuals. This process takes long time, large numbers of individuals have to be examined to obtain data for each area, and the rate of infection of sand flies with Leishmana is generally low 0.01-1% [17].…”
Section: Diagnosismentioning
confidence: 99%
“…Thus, throughout the tsetse stage of its life cycle T. brucei is in intimate contact with host tissue surfaces and exhibits an implicit requirement for sensing and signaling to guide parasite migration and differentiation. Currently, little is known about how surface contact modulates trypanosome behavior or motility [25].…”
Section: Introductionmentioning
confidence: 99%